Nilai-Nilai Pendidikan Akhlak dalam Surat Ali-Imran Ayat 159: Analisis Tafsir Ibnu Katsir dan Al-Misbah serta Implikasinya terhadap Pendidikan Islam Kontemporer - Suparmi Suparmi; Juni Beddu, Muhammad; Sumainti Sumainti (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
The moral crisis in contemporary education demands a reconstruction of moral values derived from the Qur'an as the epistemological foundation of Islamic education. This study aims to identify and analyze the moral educational values found in Surah Al-Imran, verse 159, particularly through the perspectives of Ibn Kathir’s tafsir and Quraish Shihab’s Tafsir Al-Misbah, and formulate its implications for contemporary Islamic education practices. Using a qualitative approach with a library research method, this study analyzes primary data from Ibn Kathir’s tafsir and Tafsir Al-Misbah, confronted with secondary literature on moral education theory. The analysis technique used was content analysis with a comparative-analytical approach to extract both explicit and implicit moral educational values. The findings revealed three fundamental values: first, gentleness (ar-rifq) as a humanistic pedagogical communication method; second, forgiveness (al-‘afw) as a mechanism for restoring educational relationships; third, consultation (asy-syura) as a democratic principle in educational decision-making. This study concludes that these values are not merely individual ethics but methodological principles that must be integrated into the culture of Islamic educational institutions. Practically, this requires a transformation from authoritarian-monological to dialogical-participatory educational approaches and strengthening educators' socio-emotional competencies.